1986
DOI: 10.1073/pnas.83.15.5554
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA evidence for the origin of the genus Heterogaura from a species of Clarkia (Onagraceae)

Abstract: Restriction-site variation in chloroplast DNA was examined in the morphologically distinct and monotypic genus Heterogaura and the related speciose genus Clarkia (Onagraceae), both native to California. Of the 605 restriction sites surveyed, a total of 119 mutations were identified. Of these, 55 were shared by at least two species and were used to construct a most parsimonious phylogenetic tree. This analysis, as well as one based on a distance metric, provided evidence that Heterogaura and Clarkia dudleyana, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 22 publications
6
46
1
Order By: Relevance
“…Carpenteria (Hydrangeaceae), an evergreen shrub from the Sierra Nevada, is an example of a monotypic, putatively paleoendemic genus evidently nested phylogenetically within another genus, a pattern usually associated with young taxa (e.g., Sytsma & Gottlieb 1986) and warranting taxonomic attention. Carpenteria was resolved as having diverged from within the mock oranges (Philadelphus) in the late Oligocene, after the divergence of southwestern North American taxa of Philadelphus subg.…”
Section: Wwwannualreviewsorg • Origins Of Californian Plant Diversimentioning
confidence: 99%
“…Carpenteria (Hydrangeaceae), an evergreen shrub from the Sierra Nevada, is an example of a monotypic, putatively paleoendemic genus evidently nested phylogenetically within another genus, a pattern usually associated with young taxa (e.g., Sytsma & Gottlieb 1986) and warranting taxonomic attention. Carpenteria was resolved as having diverged from within the mock oranges (Philadelphus) in the late Oligocene, after the divergence of southwestern North American taxa of Philadelphus subg.…”
Section: Wwwannualreviewsorg • Origins Of Californian Plant Diversimentioning
confidence: 99%
“…-Mean sequence divergence ranged from 0.3 to 0.4% among the three Helianthus taxa analyzed. These estimates are similar to values obtained for closely related species ofLycopersicon (0-0.7%; Palmer and Zamir, 1982), Pennisetum (0.4%; Clegg et aI., 1984), Pisum (0.1-0.8%; Palmer et aI., 1985), and Lisianthius (0-0.3%; Sytsma and Schaal, 1985b), but generally lower than es-timates obtained in Brassica (0.3-2.6%;Palmer et al, 1983), Clarkia (0.2-1.6%;Sytsma and Gottlieb, 1986), and Linum (0-6%; Coates and Cullis, 1987). However, mean sequence divergence between the two races ofH.…”
Section: Discussionmentioning
confidence: 99%
“…Because we could not detect such small changes (see also Banks and Birky [1985] and Sytsma and Gottlieb [I 986a]), we may therefore have detected only a portion of the length mutations actually present. Several investigators (Palmer, 1985a(Palmer, , 1985bPalmer et aI., 1985;Sytsma and Gottlieb, 1986a) have emphasized the difficulty in assessing whether length mutations are homologous. We therefore performed separate phylogenetic analyses that either employed or omitted these Table I]; these are difficult to interpret with purified cpDNAs, due to fragment overlap; see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The great evolutionary and phylogenetic value of cpDNA analysis has now been excellently documented at several taxonomic levels. Analysis of cp-DNA variation has clarified relationships among congeneric species, including Brassica (Erickson et al, 1983;Palmer et al, 1983), Lycopersicon (Palmer and Zamir, 1982), Lisianthius (Sytsma and Schaal, 1985), Clarkia (Sytsma and Gottlieb, 1986a), Pisum (Palmer et al, 1985), Linum (Coates and Cullis, 1987), and Cucumis (Perl-Treves and Galun, 1985). At the generic level, cpDNA data demonstrated that the monotypic Heterogaura originated from within Clarkia (Sytsma and Gottlieb, 1986b).…”
mentioning
confidence: 99%